Body Image and Exercise Habits: A Study on UIN Jakarta Female Medical Students (2020-2022) - Wilda Shafiya; Marita Fadhilah; Auliyani Andam Suri; Syarief Hasan Lutfie; Sity Kunarisasi; Muhammad Alif Adril (Faculty of Medicine, UIN Syarif Hidayatullah Jakarta, 2024)
Background: Body image refers to an individual's perception of their physical appearance, which may influence self-confidence and exercise habits. During adolescence and early adulthood, significant physical and psychological changes often result in body dissatisfaction, potentially affecting patterns of physical activity. Exercise is a structured form of physical activity intended to promote health and maintain physical fitness. This study aimed to examine the relationship between body image and exercise habits among female medical students. Methods: A quantitative analytic study with a cross-sectional design was conducted involving 100 female medical students in the academic phase (class of 2020–2022) at the Faculty of Medicine, UIN Jakarta. Participants were selected using random sampling. Data on body image and exercise habits were collected using validated questionnaires and analyzed using the chi-square test. Results: The analysis revealed a statistically significant negative association between body image and exercise habits (p = 0.006; p < 0.05). Students with a negative body image were more likely to engage in frequent exercise compared to those with a positive body image. Conclusion: Body image significantly influences exercise habits among medical students. A better understanding of this relationship may support the development of health promotion strategies that foster consistent exercise routines without reinforcing negative body perceptions.